Guanidinium-based Integrated Peptide Dendrimers: Pioneer Nanocarrier in Cancer Therapy - Singh, Dilpreet; Muhammad Irham, Lalu; Singh, Amrinder; Kurmi, Balak Das (Protein and Peptide Letters, 2024)
The landscape of cancer therapy has witnessed a paradigm shift with the emergence of innovative delivery systems, and Guanidinium-based Peptide Dendrimers have emerged as a vanguard in this transformative journey. With their unique molecular architecture and intrinsic biocompatibility, these dendrimers offer a promising avenue for the targeted delivery of therapeutic cargo in cancer treatment. This comprehensive review delves into the intricate world of Guanidinium- based Peptide Dendrimers, unraveling their structural intricacies, mechanisms of action, and advancements that have propelled them from laboratory curiosities to potential clinical champions. Exploiting the potent properties of guanidinium, these dendrimers exhibit unparalleled precision in encapsulating and transporting diverse cargo molecules, ranging from conventional chemotherapeutics to cutting-edge nucleic acids. The review navigates the depths of their design principles, investigating their prowess in traversing the complex terrain of cellular barriers for optimal cargo delivery. Moreover, it delves into emerging trends, such as personalized therapeutic approaches, multimodal imaging, and bioinformatics-driven design, highlighting their potential to redefine the future of cancer therapy. Crucially, the review addresses the pivotal concerns of biocompatibility and safety, examining cytotoxicity profiles, immune responses, and in vivo studies. It underscores the importance of aligning scientific marvels with the stringent demands of clinical applications. Through each section, the narrative underscores the promises and possibilities that Guanidinium-based Peptide Dendrimers hold and how they can potentially reshape the landscape of precision cancer therapy.
Keywords: nanocarrier